2002
DOI: 10.1097/00000637-200205000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of the Aesthetic Results and Patient Satisfaction With the Late Pedicled TRAM FlapBreast Reconstruction

Abstract: With the goal of evaluating the aesthetic results, testing the reliability of the rating systems used, and determining the patients' level of satisfaction with their breast reconstruction, pedicled transverse rectus abdominis musculocutaneous flap reconstruction was performed in 20 patients who had undergone mastectomy. The results were evaluated and compared 3, 6, and 12 months after reconstruction using the patients' own assessments (a rating of 0-10 points) and scoring by two senior plastic surgeons (using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 14 publications
2
18
0
2
Order By: Relevance
“…The aesthetic satisfaction of the patient is particularly important, as the main goal is to obtain a breast construct that appears symmetric to the contralateral breast and feels as natural as possible. 17 Rates of complications and patient satisfaction are two distinct parameters that have been used extensively in the literature to measure the success of breast reconstruction. Several determinants of patient satisfaction have been found, including type of reconstruction, 18 -20 patient age, 10,21-23 and preoperative psychological status.…”
Section: Discussionmentioning
confidence: 99%
“…The aesthetic satisfaction of the patient is particularly important, as the main goal is to obtain a breast construct that appears symmetric to the contralateral breast and feels as natural as possible. 17 Rates of complications and patient satisfaction are two distinct parameters that have been used extensively in the literature to measure the success of breast reconstruction. Several determinants of patient satisfaction have been found, including type of reconstruction, 18 -20 patient age, 10,21-23 and preoperative psychological status.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown significantly higher patient satisfaction with autologous reconstruction. [1][2][3][4][5][6][7][8][9] However, the specific aesthetic parameters of that satisfaction had not been determined. The goals of the current study were to evaluate differences in satisfaction between TRAM and implant reconstruction, to determine the specific aesthetic parameters of satisfaction, and to evaluate the effect of different variables on patients' assessment of their results.…”
Section: Discussionmentioning
confidence: 99%
“…Breast reconstruction is very important if breast cancer patients are to regain self-esteem, which helps in the recovery from illness and in the restoration of social activities. Moreover, it helps women attain an acceptable quality of life, in addition to obtaining aesthetically satisfactory features 48 . Although few studies have explored the association between quality of life and plastic surgery, a positive relationship exists between them.…”
Section: Discussionmentioning
confidence: 99%